Delayed tooth replantation after root surface treatment with sodium hypochlorite and sodium fluoride: Histomorphometric analysis in rats - Sottovia, André Dotto [UNESP]; Sonoda, Celso Koogi [UNESP]; Poi, Wilson Roberto [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Lauris, José Roberto Pereira (FapUNIFESP (SciELO), 2006)
In cases of delayed tooth replantation, non-vital periodontal ligament remnants have been removed with sodium hypochlorite in an attempt to control root resorption. Nevertheless, reports of its irritating potential in contact with the alveolar connective tissue have been described. Therefore, this study evaluated the healing process on delayed replantation of rat teeth, after periodontal ligament removal by different treatment modalities. Twenty-four rats, assigned to 3 groups (n=8), had their upper right incisor extracted and left on the workbench for desiccation during 60 min. Afterwards, the teeth in group I were immersed in saline for 2 min. In group II, root surfaces were scrubbed with gauze soaked in saline for 2 min; and in group III, scrubbing was done with gauze soaked in 1% sodium hypochlorite solution. Thereafter, root surfaces were etched with 37% phosphoric acid and immersed in 2% acidulate-phosphate sodium fluoride solution, at pH 5.5. Root canals were filled with a calcium hydroxide-based paste and the teeth were replanted. The animals were sacrificed 60 days postoperatively and the pieces containing the replanted teeth were processed and paraffin- embedded. Semi-serial transversally sections were obtained from the middle third of the root and stained with hematoxylin and eosin for histomorphometric analysis. Data were analyzed statistically using Kruskal-Wallis and Dunn's tests. The results showed that root structure and cementum extension were more affected by resorption in group III (p<0.05). All groups were affected by root resorption but the treatment performed in group III was the least effective for its control. The treatment accomplished in groups I and II yielded similar results to each other.
Keywords: Periodontal ligament; Root resorption; Sodium fluoride; Sodium hypochlorite; Tooth avulsion; Tooth replantation